Multivariate optimization of organic matter and color removal from textile dyeing industry wastewater by ultraviolet-activated oxidants - Can-Guven, Emine; Korkmaz, Mehmet Yigit; Guvenc, Senem Yazici; Varank, Gamze (ELSEVIER SCIENCE SA, 2024)
This study investigated the efficiency of ultraviolet (UV) activation of the oxidants that are used in advanced oxidation processes in textile dyeing industry wastewater treatment with high concentrations of refractory organic matter and strong color. The effect of peroxymonosulfate (PMS), peroxydisulfate (PS), hydrogen peroxide (HP), percarbonate (PC), and chlorine as oxidants in UV -based processes was first evaluated. The two processes with the greatest removal efficiency were determined as UV/PS and UV/PMS. Then the operating parameters for UV/PS and UV/PMS were optimized by the Box-Behnken Design (BBD). Process parameters for both processes were oxidant dosage, initial pH, and reaction time whereas system responses were chemical oxygen demand (COD), UV254, and color removal efficiency. Under optimum conditions in the UV/PS process (pH 5.54, PS dosage 24.4 mM, and reaction time 117 min), COD, UV254, and color removal efficiency were 83.21 %, 92.14 %, and 93.87 %, respectively. Under optimum conditions in the UV/PMS process (pH 5.83, PMS dosage 23.1 mM, and reaction time 120 min), COD, UV254, and color removal efficiency were 66.89 %, 78.45 %, and 96.89 %, respectively. The R2 of all the models that applied for the system responses of both processes was nearly one and the adj R2 values were very near to the R2 values. These findings showed that the BBD is efficient, suitable, and significant in modeling the removal of pollutants in textile dyeing industry wastewater by UV/PS and UV/PMS processes. Electrical Energy per Order (EE/O) calculations for UV/PS and UV/PMS processes were 101 and 167 kWh/m3 for optimum conditions, respectively. The results showed that both UV/PS and UV/PMS processes are effective; however, the UV/PS process is more economical and effective concerning pollutant removal efficiency and EE/O calculations.
Keywords: Advanced Oxidation; Box-Behnken Design; Industrial Wastewater Treatment; Peroxydisulfate; Peroxymonosulfate; Ultraviolet; PERSULFATE OXIDATION; HYDROXYL RADICALS; DEGRADATION; KINETICS; UV; SULFATE; MECHANISM; FENTON; Chemistry